Cidade educadora : uma construção politico-pedagógica coletiva - Santos, Daniela dos (2025)
This doctoral dissertation, entitled Educating City: a collective political-pedagogical construction, is linked to the Educational Policies research line of the Graduate Program in Education at the University of Passo Fundo and is part of the UNESCO Unitwin Chair The City that Educates and Transforms. Its general objective is to understand how the Educating City proposal has been interpreted and experienced by municipal public education managers in seven cities from the northern and mountain regions of Rio Grande do Sul, following their membership in the international Association of Educating Cities (IAEC). The study analyzes the challenges, advances, and political-pedagogical implications of this process in local contexts. The research problem is guided by the following question: how have municipal public education managers, in the investigated municipalities, interpreted and experienced the Educating City proposal through their association with the IAEC, and what challenges and advances emerge from this process in local contexts? The theoretical framework is grounded in the contributions of Freire (2001), Villar (2001), Cabezudo (2004), Charlot (2014, 2019, 2021), Bellot (2013), Pozo (2013), Moll (2004, 2013), and in the Charter of Educating Cities (2020), with emphasis on the concept of Educating City and on the perspective of education it entails. The investigation adopts the hermeneutic-dialectical perspective as its theoreticalepistemological foundation. Methodologically, it is basic in nature (Marconi; Lakatos, 2017), with a qualitative approach (Minayo, 2013). Regarding its objectives, it is descriptive-analytical (Creswell, 2007), and in terms of procedures, it is bibliographic, documentary, and based on extensive direct observation, conducted through a questionnaire (Marconi; Lakatos, 2017). Data analysis relied on the Meaning Interpretation method (Minayo, 1994, 2013). The dissertation is structured in five chapters. The first introduces the study. The second discusses the historical, political, and institutional trajectory of the Educating Cities movement, with emphasis on the constitution of the IAEC and on the trajectory of the Educating and Intelligent City Program at UPF. The third chapter is divided into two parts: the first analyzes academic production on Educating Cities in Graduate Programs in Education in Brazil; the second deepens the theoretical discussion on the concept of Educating City and the kind of education this proposal demands. The fourth chapter presents the documentary analysis (Municipal Laws) and the questionnaire. The analyses revealed normative weaknesses, plural understandings, different levels of appropriation of the proposal, and tensions between discourse and practice. The fifth chapter presents the final considerations.The research confirmed the initial assumption: the Educating City constitutes a concept-process, historically constructed and marked by contradictions, which goes beyond an institutional seal by calling upon the city to collectively, critically, and ethically assume a political-pedagogical project committed to social transformation and democracy. It also showed that although the IAEC grants the Educating City seal, it lacks mechanisms to evaluate the actual implementation of this condition after its concession.